Rural Development in Southern Manabí and the Peasant Community’s Organizational Process - Guerrero C., Fernando (Facultad Latinoamericana de Ciencias Sociales, Sede Ecuador, 2013)
This  article  deals  with  the  peasant  community  in  southern  Manabí  and  its  organizational  process during the past thirty years of rural development. Over the course of the last few decades –ever since the nineteen seventies– southern Manabí peasants have demonstrated a great ability to adapt to economic changes, through grassroots and second-level organizations, while maintaining a certain degree of resistance toward developmental intervention processes. In the face of coffee exportation and a production crisis, the peasant organizations of Manabí turned to crop diversification, short-cycle crop, pluriactivity, emigration, organizing, and establishing new institutions as a means for self-representation and in order to mediate between the peasant community itself, and public, as well as private, development entities.